EVALUATION OF EGG.YOLK-GLYCEROL COMBINATION IN TRIS, CITRATE AND PHOSPHATE EXTENDERS FOR FREEZING OF RAM SEMEN - NEMA, S P; DHAMI, A J; KAVANI, F S (The Indian Journal of Animal Reproduction, 2011)
Three buffers, viz., tris fructose citric acid egg yolk glycerol (TFCEG), phosphate buffer with glucose fructose sodium citrate potassium chloride egg yolk glycerol- a synthetic phosphate medium (Phos) and sodium citrate glucose egg yolk glycerol (SCGEG) were tested for optimum egg yolk (6, 12, 20%) - glycerol (2, 4, 6%) combination for straw freezing of Patanwadi ram semen in a 3x3x3 factorial experiment. The motility of ram spennatozoa during pre-freeze and post-thaw stages was preserved well with increasing levels of egg yolk in the medium, however, opposite was true for preservation of nonnal acrosome. Four per cent glycerol in all the three diluents could provide sufficient protection to spenn motility. However, this level was little detrimental for maintaining the acrosome integrity. The interaction of egg yolk with glycerol revealed that 12 or 20% egg yolk incorporation with 4 % glycerol level was good enough for tris and phos buffers, however, for citrate buffer 20 % egg yolk with 4 % glycerol level was optimum for freezing ram semen.